Răspuns:
Explicație pas cu pas:
x-1=11
x=11+1=12
x-3=5-x
x+x=5+3
2x=8
x=4
x/6=x-6
x=6(x-6)
x=6x-36
6x-x=36
5x=36
x=36/5
2(x-2)=3(x-3)
2x-4=3x-9
3x-2x=-4+9=5
x=5
2x+1=2
2x=2-1=1
x=1/2
x* rad din 2+1=3
x* rad din 2=2
x= 2/rad din 2=(2* rad din 2)/2=rad din 2
Este ultima de la A
x+2=3
x=3-2=1
cu prima de la A
2x+rad din 2=2* rad din 2
2x=rad din 2
x=1/2* rad din 2
2-x=3
x=2-3=-1
cu punctul 2 de la A
x=2
2x+y=6
inlocuim ec.1 in 2
2*2+y=6
y=6-4=2
punctul A
produsul mezilor=produsul extremilor
4*x=2(x+y) x=1
4=2(1+y)
4=2+2y
2y=4-2=2
y=1
punctul D